2011
DOI: 10.1074/jbc.m111.237859
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Interacts with Glucocerebrosidase Providing a Molecular Link between Parkinson and Gaucher Diseases

Abstract: The presynaptic protein ␣-synuclein (␣-syn), particularly in its amyloid form, is widely recognized for its involvement in Parkinson disease (PD). Recent genetic studies reveal that mutations in the gene GBA are the most widespread genetic risk factor for parkinsonism identified to date. GBA encodes for glucocerebrosidase (GCase), the enzyme deficient in the lysosomal storage disorder, Gaucher disease (GD). In this work, we investigated the possibility of a physical linkage between ␣-syn and GCase, examining b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(157 citation statements)
references
References 77 publications
8
145
0
4
Order By: Relevance
“…In addition, we found that mimicking αS phosphorylation increased the number of inclusions per cell. NMR spectroscopy suggests that the enhanced aggregation is due to a direct binding of Rab8a to the C-terminus of αS that has been implicated in interactions with a variety of protein partners (Burre et al, 2010;De Genst et al, 2010;Jensen et al, 1999Jensen et al, , 2000Kawamata et al, 2001;Kim et al, 2002;Yap et al, 2011). Thus, our study provides a link between physiological αS interactions and pathogenic aggregation.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, we found that mimicking αS phosphorylation increased the number of inclusions per cell. NMR spectroscopy suggests that the enhanced aggregation is due to a direct binding of Rab8a to the C-terminus of αS that has been implicated in interactions with a variety of protein partners (Burre et al, 2010;De Genst et al, 2010;Jensen et al, 1999Jensen et al, , 2000Kawamata et al, 2001;Kim et al, 2002;Yap et al, 2011). Thus, our study provides a link between physiological αS interactions and pathogenic aggregation.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to Gaucher disease, GBA1 mutation is genetically correlated with Parkinson's disease (72). It has been hypothesized that this results from the ability of β-GlcCer to promote neurotoxic amyloid formation (73,74). As we have now identified β-GlcCer as a Mincle ligand, the role of Mincle in these processes presents an intriguing issue to be addressed for the understanding of this severe progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction site has been mapped to the C-terminus of SNCA. It has also been suggested that the binding between the WT GBA and SNCA, under lysosomal conditions, could have a beneficial effect by either promoting SNCA degradation by the lysosome and/or preventing aggregation (Yap et al, 2011). The authors propose another selfperpetuating model.…”
Section: A Synucleinopathymentioning
confidence: 99%
“…The suggested beneficial interaction between SNCA and WT GBA proposed to occur under lysosomal conditions (Yap et al, 2011) may suggest that techniques to increase GCase activity and improve its delivery to the lysosome could promote degradation through the autophagy pathway and reduce SNCA concentrations.…”
Section: Autophagic Dysfunctionmentioning
confidence: 99%